Family medicine physician teachers and residents' intentions to prescribe and interpret spirometry: a descriptive cross-sectional study. (1st February 2020) - Desjardins, Audrey; Boulay, Marie-Ève; Gagné, Myriam; Simon, Mathieu; Boulet, Louis-Philippe
Abstract: Background : Spirometry is the best test to demonstrate airway obstruction, but remains underused in primary care. Objectives : We assessed, among family medicine physician teachers and residents, their intention to prescribe spirometry in patients suspected of chronic obstructive pulmonary disease and their intention to interpret the results. This evaluation is based on the theoretical framework proposed by Godin et al. for the study of factors influencing healthcare professionals' behavior. Methods : Participants of this descriptive cross-sectional study were recruited from eight Family medicine units (FMUs) of Laval University's network. They completed a 23-item self-administered questionnaire measuring their intention to prescribe and to interpret spirometry as well as some determinants of this intention (beliefs about capabilities, beliefs about consequences, social influence and moral norm). Answers to each of the items were scored on a Likert scale (score 1 to 7) where a higher score indicated a greater agreement with the statement. Results : Of the 284 eligible physicians, 104 were included. The mean score ± standard deviation of physicians' intention to prescribe spirometry (6.6 ± 0.7) was higher than to interpret the results (5.8 ± 1.5). Mean scores for all determinants of intention measured were also higher for prescription than for interpretation of spirometry. Conclusion : The results suggest that participants have a very strong intention to prescribe spirometry. Although the intention to interpret the results is positive, it is weaker than for the prescription of the test. Further studies will be needed to assess the barriers to spirometry interpretation.